PRODUKTIVITAS TRUCK CONCRETE PUMP DAN TRUCK MIXER PADA PEKERJAAN PENGECORAN BETON READY MIX - Wayan Jawat; Anak Agung Sagung Dewi Rahadiani; Ni Komang Armaeni (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
In determining the duration of a job, the things that need to be known are the volume of work and the productivity of the tool. Tool productivity depends on the capacity and cycle time of the tool. Generally the tool cycle time is set in minutes while tool productivity is calculated in production / hour. The need for heavy equipment, especially in foundry work, needs to pay attention to the number of equipment to be used so that the number of truck concrete pumps and truck mixers to be used can be balanced. Based on this, the purpose of this study is to determine the productivity of construction equipment, especially truck concrete pumps and truck mixers in ready mix concrete casting jobs in accordance with the real conditions in the field. The benefits of this research can be used as a thought contribution for educational institutions in developing and applying knowledge about the productivity of construction equipment in ready mix concrete casting jobs. In addition, providing input on the results of studies conducted as an effort to improve managerial understanding in the construction world for contractors, consultants and suppliers of ready mix concrete in the management of construction projects so as to increase competitive advantage. Data analysis method was carried out after the data collection in the field was obtained, then the analysis was carried out by performing direct calculations for cycle times for each activity of truck concrete pumps and truck mixers. Calculate the productivity of truck concrete pumps and truck mixers. Furthermore, the production capacity of truck concrete pumps and truck mixers is calculated. Calculating the duration of truck concrete pumps and determining the cost of using truck concrete pumps and truck mixers per hour. Based on the research, truck concrete pump productivity obtained was 0.521m³ / minute while the productivity of the truck mixer was 0.835 m³ / minute. This productivity was determined by cycle time, equipment conditions, work area conditions, work methods, work volume. The duration required by truck concrete pump to complete the ready mix concrete casting work on plates and beams with a volume of 65 m³ is 2,079 hours while the duration required by the truck mixer is 1,297 hours. The total truck concrete pump cost after being analyzed was obtained at IDR.376,765,212.00 while the total truck mixer cost was IDR. 4,583,876,132.00.